Politics of staging capitalist society in transcultural adaptations of brechts the threepenny opera by Ajoka theatre in Pakistan - Kayani, Taimur; Ali Termizi, Arbaayah; Wan Yahya, Wan Roselezam; Bahar, Ida Baizura (Australian International Academic Centre, 2018)
Brecht’s canonical literary work’s indigenization in Pakistan can offer a valuable transcultural adaptation study because it was performed through a radical theatre with a distinct dramaturgy and political philosophy in two different cultural contexts and historical frame of references. As the foremost representative of Brecht’s radical dramaturgy, philosophy and literary works in Pakistan since 1983, Ajoka theatre utilized these adaptations as a platform for airing a critique on capitalism in Pakistan. Prior researches focused on the formal criticism: visual and aural elements. No contextual reading is conducted to explore its political and cultural dimensions of these transcultural adaptations in providing descriptive critique on capitalist society of Pakistan. Realizing the paucity of indigenous academic work in this area this article takes this initiative and addresses this ‘research gap’ by first conducting a new historicist study of Brecht selected work and its transcultural adaptations in Pakistan. This article also investigates the theatrical and cultural factors which contributed to the enormous success of these transcultural adaptations of Brecht’s selected work in Pakistan in light of Hutcheon’s theory of adaptation.